Pengajaran Bahasa Sebagai Upaya Membangun Sikap Peduli dan Berbagi - Novia Mudzayyanah; Ni Kadek Amanda Astuti Dewi; Gideon Gary Peter Massie; I Made Adnyana Wiweka; I Made Agus Astawa; I Made Adi Widya Putra; Jordan Satria Sapta Bahari (Postgraduated Community Service Journal, 2025)
Home Welfare Karunai Illam is a nonformal social institution that focuses on empowering orphaned and underprivileged children. Through structured and enjoyable learning activities, the institution strives to foster enthusiasm for learning and develop positive character traits in the children. The community service activities carried out emphasize language teaching and money management education as a means to cultivate caring attitudes and a spirit of sharing among the children. The program is a collaboration between Warmadewa University, Universiti Tunku Abdul Rahman (UTAR) and Home Welfare Karunai Illam Malaysia. language teaching focuses on basic communication skills that are connected to social values such as empathy, cooperation, and mutual respect. The methods used are interactive, incorporating educational games, simple dialogues, and group activities that encourage children to learn while interacting positively with one another. In addition, money management lessons are provided to introduce children to simple ways of managing finances, understanding needs versus wants, and the importance of saving. Through these activities, the children are expected not only to improve their language skills but also to understand the importance of sharing, caring for their environment, and developing useful life skills. This program is hoped to become a concrete step in shaping young generations who are of good character, empathetic, and globally minded.